Answer:
The correct option is a=5, b = -4, c=7 ....
Step-by-step explanation:
The standard form is ax²+bx+c=0
where a, b, and c being constants, or numerical coefficients, and x is an unknown variable.
The given expression is:
4x + 5x2 = 8x – 7
To make it a standard equation we will move all the values to the left hand side and 0 will be left at the right hand side.
4x+5x²-8x+7=0
Now solve the like terms and arrange the equation according to the standard form:
ax²+bx+c=0
5x² - 4x +7 =0
Here a = 5
b = -4
c= 7
Thus the correct option is a=5, b = -4, c=7 ....
Answer:
P(t)=30
Step-by-step explanation:
Plug in t=6 into the equation: P(t)=t^2-t
So P(t)= (6)^2-6
P(t)=36-6
P(t)=30
What equations? Explanation:
Answer:
A
Step-by-step explanation:
given the sequence above using using two as a first term the only formula fits the sequence above is A